The Development of Online Disaster Information System Using Location Based Service (LBS) Technology - Nasaruddin Syafie; Yudha Nurdin; Roslidar Roslidar (Institute of Advanced Engineering and Science, 2014)
Indonesia is geographically located in the disaster vulnerable area and frequently hit by various disasters such as earthquake, flood, etc. So that Indonesian people aware that the disaster information system is very important. Thus, the development of information and communication technology application is needed for disaster management. For this purpose, this paper proposes on the development of online disaster information system based on location based service (LBS) technology by using short message service (SMS) gateway and global positioning system (GPS). Then,the web-based prototype of online disaster information system is designed and developed as the media to provide information of location and situation of the disaster area. Furthermore, a user interface is also designed and developed to transmit input data as the location information using manual SMS and automatically using smartphone based on SMS/GPS. The research method used in this research is a spiral method that begins with conceptual design, prototype development, application test, and evaluation. The results of this research are the web-based information system and the implemented user interface application (we called ASIKonLBS) for Android based smartphone. The online mapping of input data from smartphone to the web-based system has been tested. It shows that the disaster location information can be mapped to Google Maps timely and accurately that can be accessed using the Internet connection. The evaluation to mapping delay time shows that it is lower than the refresh time of the web-based system. Therefore, the proposed online system can be categorized as a real-time system.